1996
DOI: 10.1021/jm9601765
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Four Isomers of 4-Aminopyrrolidine-2,4-dicarboxylate:  Identification of a Potent, Highly Selective, and Systemically-Active Agonist for Metabotropic Glutamate Receptors Negatively Coupled to Adenylate Cyclase

Abstract: The four isomers of 4-aminopyrrolidine-2,4-dicarboxylate (APDC) were prepared and evaluated for their effects at glutamate receptors in vitro. (2R,4R)-APDC (2a), an aza analog of the nonselective mGluR agonist (1S,3R)-1-aminocyclopentane-1,3-dicarboxylate (1S,3R)-ACPD, 1), was found to possess relatively high affinity for metabotropic glutamate receptors (mGluRs) (ACPD-sensitive [3H]glutamate binding IC50 = 6.49 +/- 1.21 microM) with no effects on radioligand binding to NMDA, AMPA, or kainate receptors up to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…These observations led them to conclude that NMDA receptors are stimulated by the folded form of L-glutamate, while mGluRs, at least group II mGluRs, are activated by the extended form of L-glutamate. As noted before, this hypothesis was further supported by the results of (2R,4R)-APDC (15,16).…”
Section: Analogues Of Ccgsupporting
confidence: 81%
See 2 more Smart Citations
“…These observations led them to conclude that NMDA receptors are stimulated by the folded form of L-glutamate, while mGluRs, at least group II mGluRs, are activated by the extended form of L-glutamate. As noted before, this hypothesis was further supported by the results of (2R,4R)-APDC (15,16).…”
Section: Analogues Of Ccgsupporting
confidence: 81%
“…Based on these observations, several groups have carried out a modification to the structure of (1S,3R)-ACPD in order to find more potent or selective ligands. Lilly's researchers reported that an aza-substituted analogue, (2R,4R)-APDC, had about two times greater potency (EC 50 ϭ 3.5 M at human mGluR2) of activating group II mGluRs than (1S,3R)-ACPD but had little effect on group I mGluRs (15,16). Conformation studies showed that this compound preferentially adopted a fully extended glutamate conformation in the vacuum phase, which gave an additional support for the hypothesis that L-glutamate interacts with group II mGluR protein in a fully extended form (16).…”
Section: Analogues Of Acpdmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents the first example documenting the effects of a mGluR agonist; due to its potency, selectivity, and systemic activity, 32 should prove to be a useful pharmacological tool for studying the functional consequences of group II mGluR activation in vivo. 130 …”
Section: Metabotropic Glutamate Receptors (Mglurs)mentioning
confidence: 99%
“…Although DCG IV is a potent agonist at both NMDA and Group II mGlu receptors (Wilsch et al 1994;Uyama et al 1997), 2R,4R-APDC is highly selective for Group II mGlu receptors (Monn et al 1996). Thus, it seems unlikely that the results obtained in rats pretreated with APV were related to the blockade of some action of Group II mGlu receptor agonists at NMDA receptors.…”
Section: Discussionmentioning
confidence: 98%